PERAN CINTA MEREK MEMEDIASI PENGARUH KEPUASAN MEREK TERHADAP LOYALITAS MEREK PADA KONSUMEN ANOMALI COFFEE DI UBUD - Antari, Ni Kadek Dwi; Ardani, I Gusti Agung Ketut Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Brand loyalty is a strong commitment from consumers to repurchase a product or service consistently in the future. The high brand loyalty is influenced by factors including brand satisfaction and brand love. The purpose of this study was to determine the role of brand love in mediating the effect of brand satisfaction on brand loyalty. This research was conducted on consumers of Anomali Coffee in Ubud. The number of samples taken as many as 120 respondents, with a non-probability sampling technique of determining the sample using the purposive sampling method. Data was collected through questionnaires distributed online via google form. The analytical technique used is inferential statistical analysis. Based on the results of the analysis, it was found that brand satisfaction and brand love had a positive and significant effect on brand loyalty. This shows that the better the brand satisfaction and the greater the brand love, the more brand loyalty increases. Brand satisfaction has a positive and significant effect on brand love, the better brand satisfaction, the more brand love will increase. The results of the analysis also found that brand love is a mediating variable partially the effect of brand satisfaction on brand loyalty .